INTRODUCTION TO THE PHARMACY PROFESSION IN EARLY CHILDREN AT AL-HIJRAH ORPHANAGE SIGI - Muhamad Rinaldhi Tandah; Khusnul Diana; Arya Dibyo Adisaputra; Setiawati Fadillah (Journal of Health Community Service, 2022)
The pharmacist profession is closely related to drugs, both in drug manufacture, drug management and drug use in society. Introducing the pharmacist profession to the public, especially in early childhood, is important to introduce and increase early childhood knowledge on how to get, use, store and dispose of drugs properly (DAGUSIBU). This community service activity was carried out at the Al-Hijrah Orphanage, Sigi Regency with the target of all students in the orphanage. The method used was lecture method, namely by explaining information about how to get, use, store and dispose of drugs (DAGUSIBU). This service activity, it began with introducing the service team along with a description of the work being carried out, then continued by explaining the material. The material presented was about the duties and functions of pharmacists in the community, then material on how to get, use, store and dispose of drugs (DAGUSIBU). At the end of the activity, a game was held in the form of questions about the material that has been explained to the participants. There were several things about the use of drugs that are already known and knowledge was getting better after these activities were carried out.